Fatal inhalation of nitrogen inside a closed environment: Toxicological issues about the cause of death. (September 2019) - Lo Faro, Alfredo Fabrizio; Pirani, Filippo; Paratore, Antonino; Tagliabracci, Adriano; Busardò, Francesco Paolo
Highlights: Fatal inhalation of nitrogen inside a closed environment. The N2 percentages in blood samples of the deceased ranged from 80.73 to 85.23%. 27.3% of oxygenated hemoglobin and 67.4% of reduced hemoglobin were found. Autopsy and histological analysis was unremarkable. The importance of toxicological investigation in this rare kind of fatalities. Abstract: Asphyxia due to inhalation of nitrogen, as accidental or suicidal event, has been seldom reported in the forensic field. Death usually occurs because of a displacement and decrease of environmental and alveolar oxygen concentrations, but taking into account that nitrogen is a normal component of atmosphere, autopsy findings, which may be in certain cases unremarkable, must be corroborated with a careful scene investigation in order to determine the cause of death. We present a case of a 37-year old male found unresponsive inside his car with five liquid nitrogen tanks placed in the trunk, three of them with clear losses because of incomplete lock. Resuscitation efforts were unsuccessful. Autopsy findings and histological analyses were unremarkable, but toxicological analyses were crucial. Percentages of nitrogen were high in blood collected from the inferior vena cava (85.2%), left ventricle (81.01%) and the right lung (80.73%). Concentrations of nitrogen were higher than those detected in control samples: 14 autopsy cases, room air and water. The cause of death was identified as an inert gas asphyxiation, which was classified as accidental in accordance with the police report.